Fezolinetant in the treatment of vasomotor symptoms associated with menopause. (3rd July 2021) - Depypere, Herman; Lademacher, Christopher; Siddiqui, Emad; Fraser, Graeme L
ABSTRACT: Introduction : Although international clinical practice guidelines recognize a continued role for menopausal hormone therapy (HT), particularly for symptomatic women <60 years of age or within 10 years of menopause, safety and tolerability concerns have discouraged HT use due to potential links with a perceived increased risk of hormone-dependent cancers, and an established risk of stroke and venous thromboembolism. There is therefore a need for safe, effective non-hormonal therapy for relief of menopausal vasomotor symptoms (VMS). Areas covered : This narrative review summarizes the dataset accrued for fezolinetant, a neurokinin-3 receptor (NK3R) antagonist in clinical development for menopause-associated VMS. Expert opinion : Altered signaling in neuroendocrine circuits at menopause leads to VMS wherein NK3R activity plays a key role to modulate the thermoregulatory center in a manner conducive to triggering the 'hot flash' response. Thus, a new generation of NK3R antagonists has entered clinical development to specifically target the mechanistic basis of VMS. Fezolinetant is the most advanced NK3R antagonist in terms of stage of clinical development. Results to date have demonstrated rapid and substantial reduction in VMS frequency and severity and associated improvements in health-related quality of life. NK3R antagonists offer a non-hormonal alternative to HT for the treatment of menopause-related VMS.